Hierarchically flower-like WS2 microcrystals for capture and recovery of Au (III), Ag (I) and Pd (II). (August 2020) - Wang, Lun; Wang, Keming; Huang, Ruihua; Qin, Zhen; Su, Yingchun; Tong, Shanshan
Abstract: In the past few years, two-dimensional (2D) nanomaterials have emerged great potential for the removal of valuable metals and the capture of polluted-heavy metals. Herein, hierarchically flower-like microcrystals with 2D WS2 nanosheets (F-WS2 MCs) were prepared by one-pot hydrothermal synthesis strategy and its adsorption performances for precious metals were systematically assessed. The excellent adsorption efficiencies of ∼86.8%, ∼27.6%, and ∼94.1% towards Ag (I), Pd (II), and Au (III) respectively were achieved within 120 min, and the adsorption curves were in good agreement with a pseudo-second-order kinetic model showing a fast uptake rate at the optimum pH values (1.30 for Au (III), 1.43 for Ag (I), and 3.20 for Pd (II)). The adsorption isotherm followed well in the Langmuir model with the maximum removal capacities ( q max ) of 186.2 mg g −1 for Ag (I), 67.29 mg g −1 for Pd (II), and 1340.6 mg g −1 for Au (III), respectively. Furthermore, for recycling purposes, the relevant desorption solution was investigated with different ratios of monobasic acid and thiourea, suggesting the best desorption efficiency of 93.03%, 88.08%, and 85.34% for Ag (I), Pd (II), and Au (III), respectively. By characterizing the crystalline phase, and micromorphology element mapping of F-WS2 MCs before and after adsorption, the strong affinity and significant adsorption–reduction were indicated to dominate the adsorption process. Therefore, this work broadens the application range of WS2 microcrystals, providing an alternative material for capturing precious metals and wastewater treatment applications. Highlights: Flower-like WS2 microcrystals were constructed with a solvothermal method. Highly selective and efficient capture of Au (III) were achieved. The capture of Au (III) on WS2 was 1340.6 mg g −1 . Adsorption isotherm was agreed well with the Langmuir model. The adsorption mechanism can be ascribed to the adsorption–reduction interaction.